Speed control analysis of voltage source inverter fed brushless DC motor - Sudhakar, Ambarapu; Rajanna, Bodapati Venkata; Naidu, Madhireddi Bhaskara; Kumar, Munuswamy Siva; Nandaprakash, Nelaturi; Bhavana, Mukku; Kameswari, Yeluripati Lalitha (Institute of Advanced Engineering and Science, 2024)
The brushless DC (BLDC) motor requires to be controlled at the preferred speed in order to operate. A brushless DC motor's speed can be adjusted by adjusting the input voltage. In general, speed increases with voltage. The application of a Luo converter is made to satisfy the load demand, get rid of output voltage ripples, and reduce parasitic effects. The magnitude of stator input voltage to BLDC motor is controlled through the pulses applied by ATMEGA 328P micro controller to voltage source Inverter which in turn controls the magnitude of speed of BLDC motor. The position of the brushless DC (BLDC) motor is continually monitored by infrared sensors, which are then processed by a PIC16F872 microcontroller to produce the necessary pulses for BLDC motor speed regulation. The BLDC motor speed can be regulated by the pulses applied to voltage source inverter through the IR sensors placed at the motor. The outcomes of controlling the speed of a BLDC motor using voltage variation values have been shown.